STUDENT'S PERCEPTION OF TEACHER'S COMPETENCY IN LEARNING LOCAL LITERATURE IN ELEMENTARY SCHOOL - Fitri Ramadan; Arif Widodo (SocioEdu: Sociological Education, 2021)
Teacher competence is related to the teacher's ability to design learning in the classroom. One material that has a high level of difficulty is local script material. In general, students have a low interest in learning literacy lessons. Based on preliminary research at one elementary school, it is known that students' interest in learning local characters is quite high. Armed with this initial study, it is necessary to conduct further research on how teachers design local script learning in the classroom so that learning is more interesting. This study aims to describe the competence of teachers in designing local script learning from the perspective of students. The research was designed in a quantitative descriptive form with the category of survey research. The instruments used are questionnaires and interview guidelines. The data obtained were analyzed using descriptive statistics. The research location is SDN Rada, Bima Regency. The subjects of this study were students of class V totaling 30 students. The results of this study indicate that teachers have good competence in the perspective of students. Students feel happy with the varied and fun learning models. Students' perception of teacher competence in teaching is what drives students' interest in learning to be higher.